Modelo Lepto-fóbico com um bóson Z : Análise sobre possível evidência de matéria escura. - Oliveira, Jardson Ricardo de Souza (2013)
The Standard Model with its current simmetry, is complete, but still not the final word for the study of elementary particle physics, and many of the experiments show an accumulation of data indicating the existence of DarkMatter, i.e., new physics that can not be described only by it; in mid-2009 , an excess in the fraction of the flow of electron/positron experiments measured by the PAMELLA[1], FERMI[2] and HESS[3], experiments that could be interpreted as possible evidence of dark matter annihilation through Lepto-phobic interaction, instigated researchers. Therefore, to describe such a scenario, the following will consider the extension of the standard model with the gauge group ULi−Lj (1)[4], for an analysis of how this can help solve this problem of excessive flow detected.